(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Ovarian stimulation provides the foundation for subsequent assisted reproductive processes, including oocyte maturation, in vitro fertilization, embryo culture, embryo transfer, and embryo implantation. Objectives: This study aimed to describe clinical, subclinical characteristics, oocyte outcomes of ovarian stimulation protocols among the first 81 in vitro fertilization patients at Bac Giang Obstetrics and Pediatrics Hospital from May 2022 to May 2025. Materials and methods: A descriptive case series study conducted on 81 patients who had embryos available for their first embryo transfer at Bac Giang Obstetrics and Pediatrics Hospital. Conclusions: Mean age was 32.7 ± 5.4 years; secondary infertility accounted for 80.2%. The mean antral follicle count was 14.8 ± 6.8 (range: 3–36). Basal hormone levels were: FSH 7.0 ± 2.1 IU/L, LH 6.1 ± 4.2 IU/L, and AMH 3.2 ± 2.4 ng/mL. The mean stimulation duration was 9.3 days with a total FSH dose of 2382 ± 761.9 IU (600- 4500 IU). The mean number of follicles > 14 mm was 16.6 ± 9.1. The average number of retrieved oocytes was 13.2 ± 6.3. Mature oocytes accounted for 72.2%, while MI and GV stages were 10.5% and 2.7%, respectively. The mean number of oocytes used for intracytoplasmic sperm injection was 9.9 ± 5.2.